Beneficial effect of ischemic preconditioning on post-infarction left ventricular remodeling and global left ventricular function. - Papadopoulos, C; Zioutas, D; Giannakoulas, G; Matsiras, S; Karamitsos, T; Karvounis, H; Geleris, P; Stiliadis, I (2011)
BACKGROUND: Preinfarction angina (PA) is a clinical analogue of ischemic preconditioning that improves postinfarct prognosis. Data concerning the association of PA with post infarction left ventricular (LV) remodeling and LV diastolic function are limited. We aimed to evaluate this association in patients with acute myocardial infarction (AMI) in the modern clinical era of widespread use of revascularization and antiremodeling medical treatment. METHODS: We studied 53 patients with anterior AMI who underwent complete reperfusion and received up to date antiremodeling medical treatment. LV remodeling, systolic and diastolic function were assessed using 2D echocardiography at baseline and 6 at months follow-up. Patients were divided into two groups regarding the presence or absence of PA. RESULTS: LV remodeling at follow-up was less frequent in the PA group (25 vs. 55 %, P<.05). Patients with PA had lower end-systolic volume index at baseline and follow up (24.1±6 vs. 30.1±14 ml/m(2), P<.001 and 25.3±8 vs. 35.6±2 ml/m(2), P=.001 respectively). Additionally at 6 months, they had better LV ejection fraction (52.1±9 vs. 42.9±10 %, P=.002) and exhibited improved diastolic filling as reflected by mitral E/e' (14.6±5 vs. 18.8±8, P=.05). CONCLUSIONS: Ischemic preconditioning in the form of PA promotes better LV systolic and diastolic function in the mid-term and is associated with less postinfarct LV remodeling in this specific study population. The results of the study underline the possible need for further risk stratification of AMI patients regarding the absence of PA.